2014
DOI: 10.1007/s10517-014-2424-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of 5-HTR2A and 5-HTR2C Serotonin Receptor Gene Polymorphisms with Depression Risk in Patients with Coronary Heart Disease

Abstract: Associations between 5-HTR2A -1438A/G and 5-HTR2C Cys23Ser polymorphisms and depression and its severity were studied in CHD patients with consideration for the trigger factors, pathogenetic characteristics of CHD, and personal anxiety. The study was carried out in 169 men aged 31-84 (59.0 ± 8.8) years with verified CHD. Depression was more severe (Hamilton score) if it was caused by manifestation or exacerbation of CHD (nosogenic factor) and in the presence of the painful syndrome caused by the cardiac diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The possible regulatory pathway of the target genes were analyzed based on functional annotation according to KEGG pathway terms [ 15 ]. The analysis found that some important genes related to MDD, such as serine protein kinases(AKT)[ 16 ], serotonin receptors(5HT2A, HTR2C)[ 17 ], corticotrophin-releasing hormone receptor (Crhr1)[ 18 ], glutamate transporters (SCL1A2)[ 19 ], were targeted by miR-451a, miR-221-3p or/ and miR-34a-5p(data no shown). The analysis of regulatory pathway of these target genes indicated a significant enrichment in several pathways related to neuronal brain function of the depression such as PI3K-Akt signaling pathway, Axon guidance, Wnt signaling pathway, Neurotrophin signaling pathway, Hippo signaling pathway, mTOR signaling pathway, ErbB signaling pathway, Cell cycle, Apoptosis, Long-term depression(data no shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible regulatory pathway of the target genes were analyzed based on functional annotation according to KEGG pathway terms [ 15 ]. The analysis found that some important genes related to MDD, such as serine protein kinases(AKT)[ 16 ], serotonin receptors(5HT2A, HTR2C)[ 17 ], corticotrophin-releasing hormone receptor (Crhr1)[ 18 ], glutamate transporters (SCL1A2)[ 19 ], were targeted by miR-451a, miR-221-3p or/ and miR-34a-5p(data no shown). The analysis of regulatory pathway of these target genes indicated a significant enrichment in several pathways related to neuronal brain function of the depression such as PI3K-Akt signaling pathway, Axon guidance, Wnt signaling pathway, Neurotrophin signaling pathway, Hippo signaling pathway, mTOR signaling pathway, ErbB signaling pathway, Cell cycle, Apoptosis, Long-term depression(data no shown).…”
Section: Resultsmentioning
confidence: 99%
“…By receiver operating characteristic (ROC) curve analysis, let-7d-3p, miR-34a-5p, miR-221-3p and miR-451a displayed a very high sensitivity and specificity for diagnosis of MDD. In addition, our analysis of target genes and pathway of the altered miRNAs showed some important genes related to MDD, such as serine protein kinases(AKT)[ 16 ], serotonin receptors(HTR2C)[ 17 ], corticotrophin-releasing hormone receptor (CRHR1)[ 18 ], glutamate transporters (SCL1A2)[ 19 ], were targeted by miR-451a, miR-221-3p or/ and miR-34a-5p (data no shown) and several pathway related to neuronal brain function of the depression, such as PI3K-Akt signaling pathway, Axon guidance, Wnt signaling pathway, Neurotrophin signaling pathway, Hippo signaling pathway, mTOR signaling pathway, ErbB signaling pathway, Cell cycle, Apoptosis, Long-term depression, were significantly enriched by miR-451a, let-7d-3p, miR-221-3p or/ and miR-34a-5p (data no shown). We plan to investigate these target genes or proteins regulated by these altered miRNA and analyze the relationship between these target proteins and MDD in future study.…”
Section: Discussionmentioning
confidence: 99%
“…Most drugs used clinically are metabolized by cytochromes P450, specifically, CYP2A5 plays an important role in the regulation of oxidative stress in mice90. Intriguingly, the therapeutic target CYP2A5 regulates platelet activation in blood to reduce coronary heart disease in animal models91. Notably, CYP2A5 was predicted to be inhibited by 18 molecules in herbs Salvia Miltiorrhiza and Alpinia Officinarum Rhizoma , further highlighting the synergistic effect in treatment of CVDs.…”
Section: Resultsmentioning
confidence: 99%
“…It enhances the procoagulant response and increases thrombogenesis on damaged vascular surfaces. Some metaanalyses and prospective studies have concluded that 5-HT transporter linked promoter region (5-HTTLPR) polymorphisms may signi cantly impact the risk of depression in CHD patients [25][26][27][28][29]. Phillips et al [30] found that patients with depression who carry the L allele in patients after coronary artery bypass graft surgery in the United States were more likely to have adverse events; Nakatani et al [31] showed that the risk of depression and cardiac adverse events in patients with acute myocardial infarction in Japan during the recovery period is related to the S allele; Kim et al [32] proposed that Koreans carrying the S allele are related to the occurrence of post-acute coronary syndrome (ACS) depression; A prospective study by Warnke et al[28] on Germans found that 5-HTTLPR rs25531 A/G may be an important marker for detecting people at risk of late-onset depression in CHD patients.…”
Section: -Ht Transporter(5-httmentioning
confidence: 99%